2019
DOI: 10.1055/s-0039-1694759
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Psychiatric Admissions in the United States

Abstract: Objective To assess risk for postpartum psychiatric admissions in the United States. Study Design This study used the 2010 to 2014 Nationwide Readmissions Database to identify psychiatric admissions during the first 60 days after delivery hospitalization. Timing of admission after delivery discharge was determined. We fit multivariable log-linear regression models to assess the impact of psychiatric comorbidity on admission risk, adjusting for patient, obstetrical, and hospital factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Medicaid and Medicare insurance and low socioeconomic status have been associated with postpartum readmissions. 1 3 5 9 19 Non-Hispanic Black race and ethnicity—serving as a proxy for exposure to racism—has been also associated with increased postpartum readmission rates. 1 4 15 Our study found no association between race and postpartum readmission but was potentially underpowered to detect these differences given the low frequency of postpartum readmissions in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…Medicaid and Medicare insurance and low socioeconomic status have been associated with postpartum readmissions. 1 3 5 9 19 Non-Hispanic Black race and ethnicity—serving as a proxy for exposure to racism—has been also associated with increased postpartum readmission rates. 1 4 15 Our study found no association between race and postpartum readmission but was potentially underpowered to detect these differences given the low frequency of postpartum readmissions in our study population.…”
Section: Discussionmentioning
confidence: 99%